KEMAMPUAN MENULIS KALIMAT SEDERHANA DALAM BAHASA INGGRIS MELALUI METODE BERMAIN DENGAN TEKNIK MOVING AREA - ROHILAH, DEDEH (JURNAL PENDIDIKAN DASAR, 2012)
Moving Area is learning techniques adopted from the model kindergarten class consisting of areas of learning. This technique oriented activity in which the teacher provides students with a variety of games moving area so that students understand the concepts being taught with enrichment-enrichment (reinforcement) found in these areas. With this technique are expected, students can discover the excitement of learning that marked the rise of interest, full involvement, the creation of meaning, a good understanding and excellent value. In the implementation of learning to write simple sentences in English through play method by using moving area, there are several steps that must be carried out before the implementation in the classroom. Teachers create lesson plans (Lesson Plan) for each competency, arrange activities that will occur under these competencies, and designing the media, and to determine the appropriate type of evaluation.Keywords: Moving Area, Competence, Designing Media, Writing Sentences